Poor sleep quality may trigger cognitive deficits after recovery from COVID-19 - Carnes-Vendrell, A.; Piñol-Ripoll, G.; Ariza, M.; Cano, N.; Segura, B.; Junque, C.; Béjar, J.; Barrue, C.; Garolera, M.; , Nautilus Project Collaborative Group; Arauzo, Vanesa; Bernia, Jose A.; et al. (Frontiers in Psychology, 2024)
In the present study, we aimed to assess the cognition of post-COVID-19 condition (PCC) participants in relation to their subjective sleep quality (Pittsburgh Sleep Quality Index, PSQI) and to analyse possible moderators of this effect, such as quality of life (European Quality of Life-5 Dimensions, EQ-5D), fatigue (Chadler Fatigue Questionnaire, CFQ), cognitive reserve (Cognitive Reserve Questionnaire, CRC), and subjective cognitive complaints (Memory Failures of Everyday Questionnaire, MFE-30). Methods: We included 373 individuals with PCC and 126 healthy controls (HCs) from the NAUTILUS Project (NCT05307549 and NCT05307575) who were assessed with a comprehensive neuropsychological battery and various questionnaires. Results: We found that PCC participants with poor sleep quality had a 4.3% greater risk of immediate verbal memory deficits than those with good sleep quality, as indicated by the greater odds ratio (OR) of 1.043 and confidence interval (CI) of 1.023-1.063. Additionally, their risk of immediate verbal memory disorders was multiplied by 2.4 when their EQ-5D score was low (OR 0.33; CI 0.145-0.748), and they had a lower risk of delayed visual memory deficits with a greater CRC (OR 0.963; CI 0.929-0.999). With respect to processing speed, PCC participants with poor sleep quality had a 6.7% greater risk of deficits as the MFE increased (OR 1.059; CI 1.024-1.096), and the risk of slowed processing speed tripled with a lower EQ-5D (OR 0.021; CI 0.003-0.141). Conclusions: These results indicate that poor subjective sleep quality is a potential trigger for cognitive deficits. Therapeutic strategies to maximize sleep quality could include reducing sleep disturbances and perhaps cognitive impairment in PCC individuals.1. Introduction Cognition in post-COVID-19 condition (PCC) participants has been widely described.According to Soriano et al., PCC is characterized by a wide variety of symptoms that can be fixed or fluctuating, manifest 3 months after the onset of the disease, persist for at least 2 months, and cannot be explained by other diseases (Soriano et al. 2022). Studies have shown that 60% to 80% of PCC patients experience brain fog and impairment in several cognitive domains, such as attention, processing speed, memory, and executive function